Bedouin Children With Celiac Disease: Less Symptoms but More Severe Histological Features at Presentation - Yerushalmi, Baruch; Vosko, Sergei; Ling, Galina; Raanan, Ronit; Cohen, Daniel L.; Shirin, Haim; Shalem, Tzipora; Matalon, Shay; Broide, Efrat (Frontiers in Pediatrics, 2020)
Abstract Background: The prevalence of celiac disease (CD) has dramatically increased with wide variability in clinical presentations between different geographical areas. However, the contribution of ethnic disparities in pediatric celiac disease is still unclear, especially in patients of Bedouin origin. Objective: We aimed to compare the clinical presentation and histological severity of celiac disease between Bedouin and Jewish children in southern Israel Methods: This is a retrospective study in which we collected the demographic and clinical data, laboratory results, and histological severity of CD in two ethnic groups: Bedouins and Jews. The study included patients who were diagnosed between 1997 and 2015 in a tertiary hospital in southern Israel. Results: Data from 844 children with CD (271 Jewish and 573 Bedouins), 505 females (59.8%), were analyzed. Gastrointestinal symptoms and diabetes were more prevalent among the Jewish population (p<0.001 and p=0.008, respectively), while family history, failure to thrive, iron deficiency anemia, and histological severity were significantly more prevalent among the Bedouin group. Upon multivariate logistic regression analysis, only the presence of iron deficiency anemia and Bedouin origin were associated with more advanced histological disease (OR of 2.03 (95% C.I 1.31; 4.308) (P<0.009) and OR 1.78 (95% C.I 1.31; 4.308) (P<0.003) respectively). Conclusion: The clinical presentation of celiac disease in Bedouin children is characterized by anemia with less gastrointestinal symptoms, but more severe histological damage. These differences might be explained either by a delay in the diagnosis of the disease in this population or by variable environmental, cultural, and nutritional factors unique to this ethnic group.